2015
DOI: 10.3174/ajnr.a4219
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Inadvertent Intravascular Injection during CT Fluoroscopy–Guided Epidural Steroid Injections

Abstract: BACKGROUND AND PURPOSE: Inadvertent intravascular injection during epidural steroid injection can result in complications and has been investigated previously with conventional fluoroscopy, but not CT fluoroscopy. The purpose of this study was to determine the incidence of intravascular injections recognized during CT fluoroscopy-guided epidural steroid injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…It is possible that intravascular injections of steroid and analgesic occurred in these prior studies but were not detected. Kranz et al 11 reported an overall rate of intravascular injection during CT-fluoroscopic cervical TFESI similar to our own (26% versus our 24%), but with all occurrences identified only on the trial contrast injection. We may have a relatively high rate of steroid/analgesic intravascular injection because we do not use the "double tap" technique of Kranz et al to evaluate intravascular contrast washout with the trial contrast dose injection.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It is possible that intravascular injections of steroid and analgesic occurred in these prior studies but were not detected. Kranz et al 11 reported an overall rate of intravascular injection during CT-fluoroscopic cervical TFESI similar to our own (26% versus our 24%), but with all occurrences identified only on the trial contrast injection. We may have a relatively high rate of steroid/analgesic intravascular injection because we do not use the "double tap" technique of Kranz et al to evaluate intravascular contrast washout with the trial contrast dose injection.…”
Section: Discussionsupporting
confidence: 58%
“…[4][5][6][7][8][9] Although some debate remains, these complications are most commonly attributed to accidental intravascular injection of steroid. 4 The intravascular injection rate for CT-guided cervical TFESIs has previously been estimated at 1%-26%, 3,10,11 while the corresponding rate for conventional fluoroscopic guidance has been published at 17%-32.8%. [12][13][14][15] Despite the known risks of the procedure and the high anatomic resolution of CT, the role of needle position in intravascular injection has not been previously evaluated, to our knowledge.…”
mentioning
confidence: 99%
“…An intravascular injection were considered to be present if 1 of 2 contrast appearances was identified on CT-fluoroscopy, similar to previously-described criteria (11,15):…”
Section: Intravascular Injectionmentioning
confidence: 99%
“…A syringe preloaded with contrast agent (iopamidol, Isovue-M 200, Bracco Diagnostics) is then connected to the tubing, and approximately 0.2 mL is injected to assess needle tip position and potential medication spread. Intravascular injection is excluded using a double-tap technique, as described elsewhere [11]. Ideally, one notes a focus of contrast agent pooling around the needle tip that is located within the notch between the superior articular process and TP and does not change between initial and delayed images ( Fig.…”
Section: Techniquementioning
confidence: 99%